Influence of agricultural practices on nitrogen-cycling microbial communities and their interaction with mycorrhizae in Argentine Puna soils - Hernandez Guijarro, Keren; Covacevich, Fernanda; Caruso, Graciela; Castro, Dario Carlos; Feingold, Sergio Enrique (Elsevier, 2025)
Agriculture in the Argentine Puna faces significant challenges due to adverse climatic conditions and poor sandy soils prone to erosion and nutrient loss, particularly nitrogen (N), which is essential for plant growth. Despite these challenges, there is limited information on the role of beneficial soil microorganisms in nutrient cycling and uptake in this extreme environment. This study aimed to investigate the impact of agricultural practices on N-cycling microorganisms and arbuscular mycorrhizal fungi (AMF) interactions in Abra Pampa soils, located 3487 m above sea level. We conducted three annual samplings during the summers of 2020, 2021, and 2022 across four treatments: two agricultural plots (A1 and A2) amended with llama manure, each under different crop rotations - A1: Andean potato-quinoa-mallow and A2: quinoa-triticale-mallow; one soil under decomposing llama manure (BG) adjacent to agricultural plots; and a pristine control soil covered with native vegetation. We quantified the N-cycling genes (nifH, amoA from Archaea (AOA) and Bacteria (AOB), nirK, nirS and nosZ), and assessed AMF functional activity (percentage of colonization, arbuscule formation and number of spores in soil) and AMF diversity (Glomeraceae family) using PCR-SSCP analysis. Climate conditions were found to significantly influence the abundance of denitrification genes (nirK and nosZ) and AMF functional parameters, correlating with soil ammonia and nitrate concentrations. Variations in nifH abundance and the AOA/AOB ratio were associated with agricultural practices and soil parameters such as ammonia and available phosphorus content, respectively. Notably, associations between N-cycling bacteria and AMF functions suggest synergistic rather than antagonistic interactions between these groups. Agricultural activities were found to adversely affect AMF genetic diversity. The BG site emerged as a hotspot with a significant abundance of denitrification genes, warranting further investigation in future studies. This study provides valuable insights into the potential interactions among microorganisms involved in N cycling and AMF under various land use scenarios in the Argentine Puna, highlighting considerations for developing sustainable agricultural strategies in the region.